PENGARUH MODEL ACTIVE LEARNING TIPE PRACTICE REHEARSAL PAIRS TERHADAP HASIL BELAJAR SISWA X TKJ DALAM MATA PELAJARAN SIMULASI DIGITAL DI SMK NEGERI 3 PARIAMAN - Ayu Eka Putri; Edidas Edidas; Ika Parma Dewi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
The problem in this study is the low learning outcomes of students on Digital Simulation subjects in SMK N 3 Pariaman. This study aims to determine the effect of learning outcomes by using Active Learning model Practice Rehearsal Pairs type with direct learning models on subjects Digital Simulation class X TKJ odd semester SMK N 3 Pariaman Year Teaching 2017/2018. This type of research uses the Quasi Eksperimental design. Sampling using Probability Sampling technique, The sample of research is class X TKJ B as experiment class using Active Learning model of Practice Rehearsal Pairs type and class X TKJ A as control class using direct learning model. Data collection technique from post-test in experiment and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 86.88, while the control class gets an average value of 78.28. Result of hypothesis calculation at significant level α = 0,05 got titung> ttable that is 3,780> 1,678, because big tcount of ttable, hil n hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Can be concluded mean at the real level, this research shows that, there is influence of student learning outcomes between the use of Active Learning model of Practice Rehearsal Pairs type with direct learning model on Digital Simulation subjects of class X TKJ in SMK N 3 Pariaman. The use of Practice Rehearsal Pairs model has a significant influence on the improvement of Digital Simulation learning outcomes.Keywords: Active Learning, Practice Rehearsal Pairs, Learning Outcomes, Digital Simulation